2017
DOI: 10.1002/cctc.201701246
|View full text |Cite
|
Sign up to set email alerts
|

One‐Pot Synthesis of Cyclodextrin‐Doped Cu‐SiO2 Catalysts for Efficient Hydrogenation of Dimethyl Oxalate to Ethylene Glycol

Abstract: The β‐cyclodextrin (β‐CD) was successfully applied to synthesize Cu‐SiO2 catalysts by the sol‐gel method. The first and most important question addressed was increasing the copper loading with higher dispersion in the silica support. Another task was to elucidate the structure–performance relationship. Furthermore, catalysts with various β‐CD doping levels were systematically characterized and employed in the hydrogenation of dimethyl oxalate (DMO) to ethylene glycol (EG). The 0.1CD‐Cu‐SiO2 catalyst with 17.39… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 56 publications
0
33
1
Order By: Relevance
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…A catalyst that remains functionally inactive at temperatures of 40 • C or lower and activates at temperatures of 100 • C or higher is called a switchable catalyst. A wide range of technologies have been reported to realize these catalytic switching properties, including encapsulating the catalyst in compounds such as cyclodextrin [9][10][11][12][13][14][15][16]. For instance, Wang et al reported smart supramolecular nano-enzymes with temperature-driven switching properties have been successfully constructed by the selfassembly of supra-amphiphiles formed by the cyclodextrin-based host-guest chemistry [9].…”
Section: Introductionmentioning
confidence: 99%
“…sented the highest Sel. EG of 95.0% at 210 °C [22]. Chen et al have synthesized mannitol modified Cu/SiO2 catalysts by ammonia evaporation method, which showed excellent catalytic activity (average Sel.…”
Section: Introductionmentioning
confidence: 99%
“…The main stretching bands at %1100, 800, and 473 cm À1 belong to the Si─O bonds of amorphous SiO 2 support. [21] The other two peaks at 1645 and 970 cm À1 are attributed to the OH groups of adsorbed water and Cu─O─Si species, respectively. [22] The characteristic adsorption peak of copper phyllosilicate at around 670 cm À1 was not observed, indicating TOF values were calculated using Cu active sites according to the previously reported formula.…”
Section: The Analysis Of Metal Speciesmentioning
confidence: 99%